Study of Spatial Dynamics of Urban Growth Using the Geostatistical Interpolation Method of Kriging - Cruz, Fernando da Fonseca (Science and Technology: Developments and Applications Vol. 5, 2025)
The objective of this study is to simulate urban growth on the surface and underground, on a municipal scale, using a Geostatistical spatial modeling technique, called Kriging. Ordinary kriging was used as a method of geostatistical interpolation of urban growth, taking into account normal growth trends. Geostatistics is a branch of Statistics that emerged in the 1960s in France with applications to the study of the behavior of spatial phenomena, initially used for prospecting in geology and mining. Later it began to have applications in the environment and social sciences. The research work presented here aims to apply Geostatistics techniques to the dynamics of urban growth in the municipality of Oeiras, in Portugal. The results of the used method allowed us to understand the trends of urban growth on the surface and underground, as well as the advantages and usefulness of the Geostatistical technique applied to urban planning.